Sequential reform strategy: The case of Azerbaijan - Juhani Laurila; Rupinder Singh (Bank of Finland, Institute for Economies in Transition (BOFIT), 2000)
The aim is to review transition literature for evidence that supports sequential reform strategy, as presented in this report. The second part discusses the findings in the context of Azerbaijan, a formerly socialist transition economy with interesting initial conditions.Evidence of the country's current need to focus on improving public services fits well with the sequential reform view. The authors argue that constraints captured by initial conditions (human resources, administrative capacities, traditions, etc.) necessitate sequencing of reforms and outline general aspects of a sequential reform strategy designed to expedite the transition process.The literature survey supports the Washington Consensus recommendations for starting transition with macroeconomic reforms, but over time initial conditions inevitably constrain and necessitate sequencing.In other words, reform efforts initially need to be directed across the widest possible front, but later in transition the emphasis of reform efforts needs to shift from one area to another.In the later stages, emphasis needs to be laid on improvement of public sector governance to support and promote macroeconomic reforms and formation of a healthy corporate sector. Democratic institutions arise with economic growth generated by the corporate sector.
URN:NBN:fi:bof-201408072185
Keywords: 330